Failure analysis and characterization of Ferrous-Base alloy exposed in seawater environment - Mohammed Misbahul Amin; Neelofar, Amin; Kamarudin, Hussin; Che Mohd Ruzaidi, Ghazali (Universiti Kebangsaan Malaysia (UKM), 2009)
Organized by Universiti Kebangsaan Malaysia (UKM), 3rd - 4th December 2008 at Danau Golf Club, Bangi, Selangor.